A comparison of facial landmark detection methods [Yüzdeki Karakteristik Noktalari Saptama Yöntemlerinin Kiyaslanmasi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
Face analysis is a rapidly developing research area and facial landmark detection is one of the pre-processing steps. In recent years, many algorithms and comprehensive survey/ challenge papers have been published on facial landmark detection. In this work, we analysed six survey/challenge papers and observed that among open source systems deep learning (TCDCN, DCR) and regression based (CFSS) methods show superior performance. © 2018 IEEE.
Keywords: Face analysis; Facial landmarks